PTH-043 Difficult Biliary Access: Early Experience with the New Double Wire Technique Compared to Conventional Precut at Ercp. (4th June 2013) - Rameshshanker, R; Macfarlane, B; King, A; Leahy, A
Abstract : Introduction: Selective cannulation of the common bile duct (CBD) during endoscopic retrograde cholangiopancreatography (ERCP) can be technically challenging. The precut technique is a tried and tested method of gaining biliary access when standard cannulation with either contrast or guidewire has failed. However, it does have a recognised higher risk of causing pancreatitis and when used it is currently advised to place a prophylactic pancreatic stent. A new technique, termed double guidewire, involves leaving a wire in the pancreatic duct to provide a "roadmap" for subsequent biliary wire cannulation. Objectives: To report our initial experience for the success and complication rate of the double guidewire technique. Methods: Retrospective analysis of all patients who underwent ERCP between April 2010 to April 2012 at our institution. Observed differences were tested with the Fisher's exact test. Results: 484 ERCP procedures, all having initial cannulation with either a single guidewire or contrast. Overall successful biliary cannulation for first ever ERCP was achieved in 95%. Attempted CBD cannulation was facilitated by double guidewire in 20 patients and precut in 19 patients. CBD cannulation was successful in 19/20 (95%) double guidewire patients and 15/19 (79%) precut patients (p = NS). Post-ERCP pancreatitis occurred in all procedures were 11/484 (2.2%), double guidewire 3/20 (15%) (p < 0.02), precut 1/19 (5.3%). Prophylactic pancreatic stents were placed in 2 double guidewire patients and no precut patients. In the double guidewire group, patients with pancreatitis stayed longer (mean 8 days) in the hospital when compared to precut group (mean 3 days). Conclusion: Deep CBD cannulation could be equally achieved with the help of either the double guidewire or the precut technique. There was a significant increased risk of pancreatitis with the double guidewire technique presumably related to inadvertent and repeated wire cannulations of the pancreatic duct. We find that the double guidewire technique is technically easy and currently use it if pancreatic duct cannulation occurs on > 3 occasions. However, when used we now also place a prophylactic pancreatic stent at the end of the procedure. Conflicts of interest none Disclosure of Interest: None Declared.